Gender Identity, Refugeehood, and Belonging: Transgender Asylum-Seekers and International Refugee Status Determination (RSD) - Deakin, Christina Mihoko (Department of Public Law, 2023)
This research deals with transgender asylum-seekers and refugee status determination (RSD). It considers the excessively complex legal developments and discourse surrounding gender-related asylum applications and challenges the strict interpretation of the 1951 Convention Relating to the Status of Refugees and limited understandings of sex, gender, and sexual orientation by decision makers. This research adopts a queer critical analysis of international refugee law and provides a nuanced understanding of transgender identities to explain the shortcomings and misunderstandings that arise from gender-related asylum cases. This article provides recommendations for the advancements of appropriate legal approaches to gender-related asylum claims that will improve the protection of transgender asylum-seekers during the RSD process, provide a foundation for conceptual change to the asylum system, and promote the rule of law and human rights.